Effectiveness of Motor Vehicle Tax Revenue and Contribution to Local Revenue in District X - Lestari, Rahma Dwi; Mudjiyanti, Rina; Hapsari, Ira (Proceedings Series on Social Sciences & Humanities, 2025)
Motor Vehicle Tax is one of the sources of revenue that has a strategic role in supporting the financing of regional development. This study aims to analyze the effectiveness of Motor Vehicle Tax revenue and contribution to Regional Original Revenue in the X Regency Regional Revenue Management Unit for the last three years. The results showed that PKB revenue in X Regency tended to decline, as indicated by the realization achievement that approached the criteria of less effective in 2024. However, the contribution of motor vehicle tax to local revenue still shows a significant proportion, although it fluctuates every year. This finding indicates that Motor Vehicle Tax revenue has an important role in supporting the increase of Local Revenue in X Regency. Therefore, optimization of Motor Vehicle Tax revenue needs to be carried out through continuous improvement of taxpayer compliance and strengthening of the local tax administration system.